Les âges de George Sand - Westerlund, Fredrik (Bergen Language and Linguistics Studies, 2019)
The article discusses ageing and old age in three of George Sand’s texts: Indiana (1832), La Mare au diable (1846) and the first part of the novel Consuelo (1842). I use the first two parts of Pat Thane’s subdivision of age into a corporal, a cultural and a chronological component. In Sand’s fiction, the ageing female body withers, while the male body is worn. There are various reasons behind the decline. If the characters age of worries and trouble, the process can be reversed, and the persons can regain youth – at least partly – when the troubles go away. In a cultural perspective, the living conditions vary substantially between classes, specifically if the characters need to work for their living or not. Among peasants and workers, the tolerance for the age gap between spouses is narrower than in the bourgeoisie. The former risk to encounter poverty and need if the husband grows old sooner than the wife, while an elderly man of the bourgeoisie can marry a young woman in order to preserve her social status. In both classes, characters considered as old, while wise and experienced, do not longer interest anyone. Death is their future, and they ridicule themselves if they initiate long-term projects. Another stereotype, the old fool, appears as well, but in the case of Madame Carjaval, it is a role she plays to protect her niece. Many of the attitudes towards old people still exist today. The main difference vis-à-vis George Sand’s time is that, due to the development of longevity, old age arrives to people later now than in the 19th century.